Das Volk Israel und seine Gesellschaftsordnung am Berg Gottes / Sinai: Die elohistische und jahwistische Quelle in Ex 19 – Num 10 - Volgger, David (Liber Annuus, 2024)
Abstract This investigation examines the events at Sinai/Horeb as recounted in Exodus 19 – Numbers 10, focusing exclusively on the Yahwist (J) and Elohist (E) sources. While these sources exhibit distinct stylistic and thematic emphases, the analysis confirms the working hypothesis that both J and E are fundamentally shaped by six identifiable criteria of textual composition. This finding supports the proposition that both sources within the Exodus 19 – Numbers 10 narrative originated from a shared socio-cultural milieu and likely emerged within a relatively close temporal proximity. Consequently, the textual segments attributed to J and E within this narrative can be characterized as a “source compilation.”